Primary Dysgerminoma of the Uterine Cervix: A Rare Case Report - Biruck Gashawbeza; Bethel Dereje; Ferid A. Abubeker (Hindawi Limited, 2024)
Introduction. Primary extragonadal germ cell tumors (EGCTs) are a very rare clinical encounter most commonly reported in males. Among females, the placenta, pelvis, uterus, brain, and mediastinum are the most common extragonadal sites and predominantly display nondysgerminoma histology. In this report, we present a case of a primary cervical dysgerminoma in a young female patient. Case Report. An 18-year-old nulligravid woman presented with a 12-month history of vaginal bleeding and discharge. Routine blood tests and serum levels of tumor markers were within normal limits. The chest X-ray was normal. A high-resolution pelvic MRI showed a well-defined lobulated cervicovaginal mass measuring 8×6×5 cm expanding into the vaginal canal with mild homogenous contrast enhancement. An incisional biopsy was performed vaginally under anesthesia, and histologic findings were consistent with dysgerminoma. A repeat follow-up pelvic MRI was done and showed a reduction in the size of the mass by more than 70%. The patient was treated with 4 cycles of bleomycin, etoposide, and cisplatin chemotherapy. Additional external pelvic beam radiation treatment was administered for a partial response. After 3 months of radiotherapy, a contrast abdominopelvic CT scan showed a recurrent cervicovaginal mass with extension to the pelvic sidewalls. The patient was initiated with ifosfamide, paclitaxel, and cisplatin (ITP) as second-line chemotherapy for a recurrent germ cell tumor but later died from hydronephrosis, chronic anemia, and sepsis. Conclusion. The uterine cervix is a very unusual site for primary dysgerminoma and can have a very aggressive clinical course. A high index of suspicion and an exhaustive workup are necessary to reach a diagnosis, particularly in a young patient presenting with a cervical lesion.